Implementasi Program Keluarga Harapan (PKH) Dalam Menanggulangi Kemiskinan (Studi Kasus Di Kecamatan Pariaman Timur Kota Pariaman - Syahrial, Syahrial; Desrina, Thazilla (CV. ITTC INDONESIA, 2021)
The Family of Hope Program (PKH) is a program for providing conditional social assistance to families and someone who is poor and vulnerable who are registered in the integrated data program for handling the poor and processed by the Center for Social Welfare Data and Information which is designated as Beneficiary Families (KPM). This study aims to analyze the implementation of the Family Hope Program (PKH) in overcoming poverty in the East Pariaman District, Pariaman City. This type of research is a descriptive study using a qualitative analysis approach. The data collection technique was carried out by direct observation to the research location and interviewing predetermined research respondents. Respondents of this study were the Social Service, Coordinator of PKH in Pariaman City, PKH Facilitator in East Pariaman District. Based on the results of the research, the implementation of the Family Hope Program (PKH) in reducing poverty in Kota Pariaman has been running well, but has not been on target. When viewed from the condition of PKH beneficiaries, they use it to help with health, education and social costs and make PKH participants aware of the importance of education and health services.